On computing critical delay for fixed mode radius: Centralized and decentralized control - Sahoo P.R.; Ghosh S. (My University, 2025)
Fixed mode radius is a perturbation measure used to represent how ‘close’ a system is from having at least one fixed mode. In this paper, a catalog of measures for critically delayed fixed mode radius that correspond to critical delays having minimum radius is introduced for systems with input and output delays. Computable formulas are derived using perturbation measures for both centralized and decentralized control systems. Numerical examples are presented to demonstrate the critical delay feature. © 2020 Elsevier B.V.